2009
DOI: 10.3347/kjp.2009.47.1.13
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Dung Beetles Infected with Larval Nematodes with Particular Note on Copris lunaris Beetles as a Vector for Gongylonema sp. in Iran

Abstract: Dung beetles (family Scarabaeidae) are one of the largest families of beetles worldwide. Due to biological behavior of these arthropods, they are considered to play an important role in the life cycle of some helminths. In the present study, dung beetles collected from cattle pastures in rural areas of Ardabil province, north-west of Iran were examined for infection with larval stages of helminths. According to the results, nematodes of 2 genera were identified including Rhabditis and Gongylonema. The more com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…humanus. This is in agreement with results reported by Mowlavi et al (2009) who found similar Gongylonema sp. larvae in naturally infected Gy.…”
Section: Resultssupporting
confidence: 95%
See 1 more Smart Citation
“…humanus. This is in agreement with results reported by Mowlavi et al (2009) who found similar Gongylonema sp. larvae in naturally infected Gy.…”
Section: Resultssupporting
confidence: 95%
“…The genus Gongylonema Molin, 1857 (Order Spirurida, Family Gongylonematidae) has species that affect wild and domestic mammals and birds (Mowlavi et al , 2009). The life cycle is indirect with coprophagous arthropods as intermediate hosts (Anderson, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Gongylonema sp. is a spirurid nematode of vertebrate hosts with an indirect mode of transmission, usually through insect vectors (Mowlavi et al 2009). We recorded the presence of these species in all the mammalian hosts studied except the wild boar (n=8), stripe-necked mongoose (n=2), wild dog (n= 2) and leopard (n=2).…”
Section: Discussionmentioning
confidence: 99%
“…However, dung beetle infection with Gongylonema spp. has been recorded in Northwestern Iran [33]. Studies have documented presence of S. armeniacus in Central and Northern Iran [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The beetles have been reported individually as positive or negative for larval stages of helminths. For positive beetles, larvae were removed and transferred into normal saline on ice for 1 h to relax and immobilize [33]. Removed larvae were transferred into lactophenol and 70% ethanol for morphological and molecular studies.…”
Section: Morphological Analysis Of the Recovered Larvaementioning
confidence: 99%